Impact Resistance Performance of Kenaf Fibre Reinforced Concrete - Muda Z.C.; Mohd Kamal N.L.; Syamsir A.; Sheng C.Y.; Beddu S.; Mustapha K.N.; Thiruchelvam S.; Usman F.; Alam M.A.; Birima A.H.; Zaroog O.S. (Institute of Physics Publishing, 2023)
Concrete slabs; Concretes; Cracks; Drops; Fiber reinforced materials; Fibers; Hemp; Kenaf fibers; Mesh generation; Crack resistance; Drop weight impact; Fiber diameters; Fibre reinforced concrete; Impact resistance performance; Linear relationships; Mesh reinforcement; Projectile tests; Reinforced concrete; crack; diameter; impact; performance assessment; reinforced concrete; research work; slab; spacing; stress resistance; weight; Fibers; Kenaf; Reinforced Concrete; Hibiscus cannabinus